GAMBARAN POLA KONSUMSI DAN STATUS GIZI BADUTA (BAYI 6-24 BULAN) YANG TELAH MENDAPATKAN MAKANAN TAMBAHAN TABURIA DI KELURAHAN KEMENANGAN TANI KECAMATAN MEDAN TUNTUNGAN TAHUN 2012 - Mona Sylvia Junita; Albiner Siagian; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Taburia means supplemental food of multivitamin and multimineral to fulfill nutrient needs and the growth for the babies aged 6-24 months.  Taburia is as the expansion of local product of micronutrient powder (MNP) and as the strategy to overcome the anemia as the effect of iron deficiency and other micro nutrient deficiencies. The objective of this research was to know the description of consumption pattern and nutrient status of the babies aged 6-24 months getting Taburia in  Kemenangan Tani  area,  Medan Tuntungan, Medan City in 2012. This research was quantitative descriptive with Cross sectional design. The results of research showed that consumption pattern of the babies  aged  6-24  months  based on  the category of food  menu was categorized  good for  67,7% and  consumption pattern of the babies aged 6-24 months based on  the category of eating  frequency was categorized good for 53,2%, whereas based on  the weight  per age  was categorized  normal  for 57,6%, nutritional  status based on height  per  age was categorized normal for 68,1% and nutritional status based on weight per height  was categorized normal  for 73,0%. Taburia administration program may enhance nutritional status of two years old of the babies into normal. Hence, it is expected that Health Department should continue Taburia  administration program since it is proved that  it may enhance  nutritional  status of  two years old of  the babies in Kemenangan Tani area, Medan Tuntungan and also it is expected that Primary Health Center is more active in giving  the socialization of  information and counseling about good consumption pattern of the baby and  Taburia administration.